Benthic seaweed off the southern coast of Nayarit, Mexico - Mateo-Cid, Luz Elena; Mendoza-Gonzalez, A. Catalina (Instituto de Ecología, A.C., 1992)
Results are presented of a study on benthic marine algae from the south coast of Nayarit, in the tropical waters of the Mexican Pacific. The floristic list includes data on distribution of the species, reproductive stage, tidal level, mode, facies and epiphytism. Two species of Cyanophyceae, 69 species of Rhodopgyceae, 16 species of Phaeophyceae, 3 species of Bacillariophyceae and 29 species of Chlorophyceae were identified. The Rodophyceae were dominant in terms of diversity. Species diversity in relation to facies, temperature, light and tides is also discussed.